Design and Analysis of Grape Cold Storage Model Using IoT Based Technology - Shah, Abhijeet; Gaurvadkar, Amey; Patil, Sukanya (Journal of the Institution of Engineers (India) Series C, 2025)
A miniature replica of a grape cold storage facility has been constructed to optimize air distribution and temperature uniformity using computational fluid dynamics (CFD) analysis. CFD simulations were conducted to evaluate and enhance airflow patterns and thermal distribution within the storage model, ensuring efficient cooling performance. In addition, Internet of Things (IoT) technology was integrated to monitor real-time temperature and humidity levels, with sensor data being transmitted to the cloud for remote access and monitoring. The model utilizes a Node MCU board, DHT11 temperature sensor, and a humidity sensor, showcasing a cost-effective and efficient solution for cold storage optimization. The findings highlight the importance of CFD analysis in determining optimal duct configurations and airflow distribution, complemented by IoT-based real-time monitoring to maintain controlled storage conditions.